PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH PADA BANK SAMPAH NGUDI LESTARI KELURAHAN TINJOMOYO KOTA SEMARANG - Nurhusna, Nabila; Kismartini, Kismartini; Suwitri, Sri (Journal of Public Policy and Management Review, 2024)
Semarang City Regulation Number 2 of 2014 Article 39 paragraph (1) states that the community participates in the decision-making, implementation, and supervision processes in household waste management activities as well as similar waste management conducted by the Regional Government. Waste management can be realized through waste bank activities which require community participation. Ngudi Lestari Waste Bank is one of the waste banks in Semarang City that requires community participation, ranging from contributions to waste management responsibilities. This study aims to analyze community participation and identify the driving and inhibiting factors of community participation in waste management at Ngudi Lestari Waste Bank. Data collection techniques include observation, interviews, and documentation. The data obtained are analyzed using triangulation techniques. The results show that the community has participated in contributions, organization, roles, actions, and responsibilities, but overall, it has not been maximized due to several waste management stages carried out by waste bank officers. The biggest driving factor for community participation is internal factors such as willingness, ability, and awareness, while external factors are driven by mass media. Internal factors that do not hinder participation include employment, education, and gender, while external factors that hinder participation include mass media. It is hoped that the waste bank can make various efforts to increase community participation in the future so that waste bank activities can run smoothly and maximally.